Bone defect regeneration with bioactive glass implantation in rats - Macedo, Nelson Luiz De [UNESP] (2004)
The main goal of this study was to histologically evaluate the healing of surgically created defects on the tibiae of adult male rats after implantation of two types of bioactive glass. Sixteen adult Wistar rats (body weight of 300g) were divided into two groups: PerioGlas (PG) (n=8) and BioGran (BG) (n=8). Unicortical bone defects with 3-mm diameter were performed in both tibiae of the animals and filled with two types of glass particles. The rats were then sacrificed at 7, 14, 30 and 60 days, and the tissues were prepared for histological processing, sectioning, and staining with hematoxylin and eosin, as well as Mallory trichrome, and analyzed under light microscope. Within 7-14 days, both groups presented connective tissue septa with new bone formation, more intense in the PG group. In the subsequent periods (30 and 60 days), both groups presented more mature bone tissue around the glass particles. Bone trabeculae formed in all experimental periods were juxtaposed to the glass particles. It can be concluded that both materials promoted comparable bone formation over the entire extension of the defect, independently of the size of the granules, thus confirming their biological osteoconductive property.